Peripheral facial palsy caused by neoplastic meningitis. (2nd May 2014) - Hiraumi, Harukazu; Yamamoto, Norio; Sakamoto, Tatsunori; Ito, Juichi
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To describe the clinical presentation of peripheral facial palsy caused by neoplastic meningitis. Study Design Retrospective case series. Methods Retrospective review, including accompanying symptoms and magnetic resonance imaging (MRI) findings. Results Between January and December 2011, six patients were diagnosed with peripheral facial palsy caused by neoplastic meningitis. The patient age at presentation ranged from 56 to 77 years. The tumor origins were as follows: malignant lymphoma (n = 3), lung cancer (n = 2), and kidney cancer (n = 1). In three patients, sudden sensorineural hearing loss accompanied the facial palsy. Three patients were judged to be tumor‐free at the onset of the facial palsy. In two patients, the malignancy was not diagnosed at the onset of facial palsy and hearing loss. Only one patient was diagnosed as having a tumor at the onset of the facial palsy. On the MRI, a mass lesion was detected in the internal auditory canals (IAC) of four patients; one had a solitary IAC tumor. In this patient, the diagnosis required a histopathological study using a translabyrinthine approach. In the other two patients, the facial nerve was enhanced with gadolinium, but it was difficult to differentiate the observed condition from Bell's palsy. In these patients, repeated cytological studies led to the correct diagnoses. Conclusions The clinical symptoms and MRI findings of peripheral facial palsy caused by neoplastic meningitis sometimes mimic those of benign facial palsy. Level of Evidence 4. Laryngoscope, 124:2139–2143, 2014